The effect of different desalting methods on the quality of injected brine and pickle salted frozen cod (Gadus morhua) ... - Dargentolle, Cécile; Sveinsdóttir, Hildur Inga; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
The demand for ready-to-use desalted or rehydrated products have increased, creating a need for large-scale industrial production of desalted products. In order to adjust to market requirements, the desalting phase must therefore be included in industrial operations. The effects of three different desalting methods (control, movement, flow) for both brine and pickle salted cod on quality parameters of the resulting desalted samples have been studied (Mohammed Raheem Waheed Almozani, 2021) on desalting yield, cooking yield, colour, texture, salt content, water content, and desalting time. The purpose of this report was to evaluate if freezing and frozen storage of six months at -25°C of the desalted cod had an influence on its properties as compared to the unfrozen desalted samples. Freezing had an impact on the properties of both on the desalted brine salted and pickle salted samples regarding the texture changes, as well as the salt repartition in the samples. Impact on the yellow colour was also ...